Estrategias empleadas en las provincias imperiales: perspectivas prehispánicas y coloniales en Mesoamérica - Chance, John K.; Stark, Barbara L. (Revista Española de Antropología Americana, 2007)
We explore concepts and evidence relating to strategies employed by people in imperial provinces, using archaeological and ethnohistoric evidence from Mesoamerica. For convenience, we refer to these as provincial strategies. By contrasting Late Postclassic data for the Aztec empire and Colonial data for the Spanish empire in Mexico, we explore their commonalities and differences to advance a more systematic understanding of provincial strategies. Our approach rests on the premise that, just as imperial powers had strategies for administering their subjects, the provincial subjects also employed various strategies for protecting and improving their position within the empire. Nine provincial strategies operative in Mesoamerica were affected by geographic distance and environmental factors, duration of imperial rule, social class, and differences in the economic and social integration of subject populations.